Integration Through Affordability - Exploring inclusionary housing strategies in New York City and Gothenburg, Sweden - Gibbs, Jason (My University, 2020)
Many Americans view Sweden as a model of equality, with a system of universal welfare that provides for the well-being of all citizens. However, Sweden is in the midst of a housing crisis, and residents with lower incomes are especially impacted by the effects of the market turn taken in recent years. Yet still the ideal of a universal system holds tremendous power, and stakeholder options are limited for targeting housing to residents with lower incomes. Many low-income residents of the United States also have difficulty accessing adequate and affordable housing, but the U.S. has a long history of a dual housing system, with private market-driven housing supplemented by selective programs for those in need. In recent decades localities in many countries have adopted inclusionary housing policies as a way to combat segregation and incentivize the private sector to create housing that is affordable for residents with lower incomes. Inclusionary housing policies generally imply a selective, means-tested approach, as the low-rent dwelling units created are typically reserved for residents with low incomes. The Swedish system historically has not had this type of selective housing, but in Gothenburg the municipality is experimenting with using the land allocation process to spur the creation of low- and mixed-income housing. This thesis project explores the housing regimes of Gothenburg and New York City through the perspective of housing for people who have low incomes, examines the structure of inclusionary housing policies in New York City, and investigates Gothenburg’s recent experiments with inclusionary housing.
Keywords: inclusionary housing; affordable housing; housing policy; housing regimes